First results from HECTOR: High EffiCiency TOtal absorption spectrometeR for γ-process nucleosynthesis studies. (October 2020) - Simon, A; Kelmar, R; Millican, P; Olivas-Gomez, O; Reingold, C S; Anderson, T; Churchman, E; Clark, A M; Cooper, N; Dombos, A C; Frentz, B; Henderson, S L; et al.
Abstract: The nucleosynthesis path of the γ -process is predominantly governed by the branching points at which the flow of the initial ( γ, n) is redirected by either ( γ, p) or ( γ, α ) reactions. In this work, the inverse reactions, proton and α capture on 108 Cd were studied in order to aid in verification of the 112 Sn isotope as a potential branching point in the γ -process. The results of the first measurement with a γ -summing detector, HECTOR, are compared with previous measurements found in the literature and with NON-SMOKER predictions. The results of this work will provide input for Hauser-Feshbach calculations to obtain the γ induced reaction rates.